Letter from J.C. Godsey, regarding JSU's ROTC, March 1969 - Godsey, J. C. (JSU Digital Commons, 1969)
Letter from J.C. Godsey, Fort McPherson, GA regarding an amendment of existing supplemental agreements for supply, accounting, and other procedures for JSU’s ROTC, March 14, 1969. Enclosed is a supplemental agreement. (letter dated March 14, 1969) https://digitalcommons.jsu.edu/rotc_docs/1016/thumbnail.jpg